2018
DOI: 10.1371/journal.pgen.1007593
|View full text |Cite
|
Sign up to set email alerts
|

MiR-202 controls female fecundity by regulating medaka oogenesis

Abstract: Female gamete production relies on coordinated molecular and cellular processes that occur in the ovary throughout oogenesis. In fish, as in other vertebrates, these processes have been extensively studied both in terms of endocrine/paracrine regulation and protein expression and activity. The role of small non-coding RNAs in the regulation of animal reproduction remains however largely unknown and poorly investigated, despite a growing interest for the importance of miRNAs in a wide variety of biological proc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 78 publications
5
81
0
Order By: Relevance
“…Interestingly, in vitro functional study of miR-130b showed the involvement of this miRNA in oocyte maturation by regulating the SMAD5 and MSK1genes [44]. Similarly, other studies have shown the role of miR-318 [45], miR-202 [46] and let-7, miR-278 [47], miR-378 [48] and miR-125a-3p [49] during oogenesis.…”
Section: The Role Of Cellular Mirnas In Follicular Development and Oomentioning
confidence: 82%
“…Interestingly, in vitro functional study of miR-130b showed the involvement of this miRNA in oocyte maturation by regulating the SMAD5 and MSK1genes [44]. Similarly, other studies have shown the role of miR-318 [45], miR-202 [46] and let-7, miR-278 [47], miR-378 [48] and miR-125a-3p [49] during oogenesis.…”
Section: The Role Of Cellular Mirnas In Follicular Development and Oomentioning
confidence: 82%
“…In the present study, miR-202-5p localized to both germ and somatic lineages in juvenile testes and ovaries of Atlantic salmon and was highly abundant in somatic supporting cells in mature testes ( Figure 5 and Figure S5). In medaka, miR-202-5p is abundant in unfertilized oocytes and in the follicular cells of the ovary, and is essential for the regulation of oogenesis [38]. Together, these results suggest a conserved role of miR-202-5p in reproductive processes in teleost gonad development during gamete maturation, and indicate supporting somatic cell origin of miR-202-5p in a mature gonad.…”
Section: Mirna Heterogeneity In Sperm Fractionsmentioning
confidence: 63%
“…This potential interplay between circRNA and miRNA could provide a reference for elucidating regulatory mechanisms of these DECs in oocyte meiotic maturation. Indeed, recent studies have shown that maternal miRNA participates in regulating oocyte maturation and early embryo development in several species, including pigs (Wright et al, 2016), medaka (Gay et al, 2018), and C.elegans (Minogue et al, 2018). Specifically, miRNA-7 was found to inhibit epidermal growth factor receptor (EGFR) expression in human cancer cells (Webster et al, 2009) and EGFR signaling is required for cumulus cell expansion and oocyte maturation (Prochazka et al, 2017), suggesting that miRNA-7 may negatively regulate oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the imperfectness of in vitro culture conditions currently used that cannot achieve the optimal maturational outcomes, and there is inadequate information regarding the unique molecular mechanisms of porcine oocyte meiotic maturation (Sun and Nagai, 2003; Prather et al, 2009). It is known that oocyte maturation is intricately regulated by cumulus cell or oocyte itself derived non-coding RNAs, such as microRNA (miRNA) (Dallaire and Simard, 2016; Wright et al, 2016; Li et al, 2017b; Gay et al, 2018; Minogue et al, 2018), endogenous small interference RNA (siRNA) (Suh et al, 2010) and long non-coding RNA (lncRNA) (Taylor et al, 2015). Recently, circular RNA (circRNA) has received increasing attention in multiple biological research fields.…”
Section: Introductionmentioning
confidence: 99%